Preparation and characterization of paraffin/nickel foam composites as neutron-shielding materials. (March 2018) - Zhang, Yun; Chen, Feida; Tang, Xiaobin; Huang, Hai; Ni, Minxuan; Chen, Tuo
Traditional neutron-shielding materials usually have poor mechanical properties and secondary gamma-shielding capability. The new requirements of modern neutron-shielding materials are difficult to satisfy. A paraffin/nickel foam neutron-shielding composite was prepared and characterized in this study. Open-cell nickel foams were fabricated through electrodeposition. Subsequently, the paraffin/nickel foam composite were prepared by filling the open-cell nickel foams with melted paraffin. The intrinsic parameters of nickel foam and the content of neutron absorber (boron carbide) were controlled to optimize the composite. The mechanical properties of the composite were studied through a static compression test. The compressive strength improved to 0.4 times that of the nickel foams. The Am–Be source transmittance experiment showed that the 8 cm thick PFM presented a neutron transmittance of 56.1%, and the 6 cm thick boron carbide/paraffin/nickel foam (PFM-B) presented a neutron transmittance of 37.6%. The paraffin/nickel foam and PFM-B had approximately the same shielding efficiency as paraffin and boron carbide/paraffin, respectively. However, the second gamma ray shielding efficiency of the paraffin/nickel foam and PFM-B was significantly higher than that of paraffin and boron carbide/paraffin. The mechanical properties and secondary gamma ray-shielding capability of the composite can be improved by increasing the relative density of nickel foams.